Amelogenin Exon4 Forms a Novel miRNA That Directs Ameloblast and Osteoblast Differentiation. (April 2016) - Le, M.H.; Warotayanont, R.; Stahl, J.; Den Besten, P.K.; Nakano, Y.
Amelogenins constitute the major portion of secretory enamel matrix proteins and are known to be highly alternative spliced. Of all the alternatively spliced forms of amelogenins, exon4 is most commonly spliced out. Our analyses of the exon4 sequence led us to hypothesize that when spliced out, exon4 may generate a novel mature miRNA. To explore this possibility, we used in vivo mouse models (wild-type and Amel knockout mice) and in vitro cell culture to investigate the presence and function of a mature miRNA derived from exon4 (miR-exon4). When ameloblast-like cells (LS8) were transfected with an amelogenin minigene to increase amelogenin synthesis, the transfected cells synthesized miR-exon4. Introduction of a mutation in the conserved CNNC sequence required for primary miRNA recognition, downstream of the mature miR-exon4 sequence, resulted in a significantly reduced production of miR-exon4 in the transfected cells. In vivo, miR-exon4 was most highly amplified from wild-type mouse enamel organs at the secretory stage. In Amel knockout mice, an in vivo model for reduced amelogenin synthesis, we found reduced miR-exon4, with no changes in expression of enamel matrix–related genes. However, expression of Runx2 and its downstream genes Odam and Amtn were significantly downregulated. Transfection of miR-exon4 mimic to the LS8 cells also significantly upregulated Runx2 . The mature miR-exon4 as well as Runx2 was also present in mouse osteoblasts with no apparent change in expression level between wild-type and Amel knockout mice. However, transfecting miR-exon4 inhibitor to the MC3T3-E1 osteoblastic cells resulted in a significant downregulation of Runx2 expression. These data indicate that when exon4 is spliced out, as occurs most of the time during alternative splicing of amelogenin pre-mRNA, a novel mature miRNA is generated from exon4. This miR-exon4 may contribute to the differentiation of ameloblasts and osteoblasts through regulation of Runx2 expression.